Evaluation of the Bond Strength of Denture Base Resins to Acrylic Resin Teeth: Effect of Thermocycling - Marra, Julie; de Souza, Raphael Freitas; Barbosa, Débora de Barros [UNESP]; Pero, Ana Carolina [UNESP] [UNESP]; Compagnoni, Marco Antonio [UNESP] (Wiley-Blackwell, 2009)
Purpose: The purpose of this study was to evaluate the thermocycling effects and shear bond strength of acrylic resin teeth to denture base resins.Materials and Methods: Three acrylic teeth (Biotone, Trilux, Ivoclar) were chosen for bonding to four denture base resins: microwave-polymerized (Acron MC), heat-polymerized (Lucitone 550 and QC-20), and light-polymerized (Versyo. bond). Twenty specimens were produced for each denture base/acrylic tooth combination and were divided into two groups (n = 10): without thermocycling (control groups) and thermocycled groups submitted to 5000 cycles between 4 and 60 degrees C. Shear strength tests (MPa) were performed with a universal testing machine at a crosshead speed of 1 mm/min. Statistical analysis of the results was carried out with three-way ANOVA and Bonferroni's multiple comparisons post hoc analysis for test groups (alpha = 0.05).Results: The shear bond strengths of Lucitone/Biotone, Lucitone/Trilux, and Versyo/Ivoclar specimens were significantly decreased by thermocycling, compared with the corresponding control groups (p < 0.05). The means of Acron/Ivoclar and Lucitone/Ivoclar specimens increased after thermocycling (p < 0.05). The highest mean shear bond strength value was observed with Lucitone/Biotone in the control group (14.54 MPa) and the lowest with QC-20/Trilux in the thermocycled group (3.69 MPa).Conclusion: Some acrylic tooth/denture base resin combinations can be more affected by thermocycling; effects vary based upon the materials used.
Keywords: Shear strength; acrylic resins; artificial tooth; dental materials